Full-field shear analyses of sandwich core materials using Digital Image Correlation (DIC). (1st March 2015) - Fathi, Amir; Keller, Jan-Hendrik; Altstaedt, Volker
Abstract: Mechanical properties and global stability of foam core sandwich structures are highly controlled by the shear response of the core material. In this work, we have studied the shear deformations of three common structural core materials with the aid of full-field optical analysis. The chosen core materials are namely extruded PET foam ( ρ  = 105 kg/m 3, G xz  = 21 MPa, ) and cross-linked PVC foam ( ρ  = 60 kg/m 3, G xz  = 22 MPa) which have comparable shear properties, as well as Balsa wood with the lowest density commercially available ( ρ  = 94 kg/m 3, G xz  = 106 MPa) as a reference core material. Both global and local shear strains in the core materials are calculated and graphically visualized. In the elastic region, foam cores showed more uniform deformations than Balsa. Yielding and shear failure of the two foam core materials were quite different. The PVC foam experienced a high local deformation under the load introduction bars, from which sub-interface shear failure initiated. The PET foam, in contrast, showed no sign of stress concentrations, resulting in a homogenous evolution of shear deformations in the mid-core regions. A comparison between the direct foam shear test and sandwich specimen bending suggested that the former method might not be capable of capturing a full picture of the in-service core shear response.